IFRSs : a visual approach (Basingstoke, UK : Palgrave Macmillan, 2010)
This edition of 'IFRSs -- A Visual Approach' provides a structured overview of all International Financial Reporting Standards (IFRSs), i.e. IFRS 1 to IFRS 9, IAS 1 to IAS 41 and the related Interpretations issued by the International Financial Reporting Interpretations Committee (IFRIC), i.e. IFRIC 1 to IFRIC 19, as at 1 January 2010. The book links each line in the financial statements to the chronologically numbered Standards and then summarises in diagrams each of those Standards to help the reader visualise the key decisions and choices that their application requires. It is an excellent introduction for those seeking a high level overview and a readily accessible guide to the pronouncements for those wanting to enhance their understanding. By incorporating references to the Standards and Interpretations, it provides a tool to allow more experienced users to quickly identify relevant guidance. This book will be useful for students, those involved in the preparation of financial statements, CFOs, non-executive directors, business journalists, management consultants and many others. Even advanced users wishing to keep abreast of the most recent developments will find that the guide allows them to quickly focus their further research
BSBA
Keywords: International Financial Reporting Standards; Financial statements; Accounting; Financial statements